2007
DOI: 10.2753/eee0012-8775450301
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Disparities in Productivity in Central and Eastern Europe

Abstract: This paper examines the evolution of territorial imbalances in productivity in 39Central and Eastern Europe regions between 1992 and 2001. The results obtained show an overall reduction in regional inequality over the study period. This process was compatible with the simultaneous presence of between-country convergence and within-country divergence. In any event, the polarisation of the distribution under consideration is seen to decrease, while the registered level of intra-distribution mobility is relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
2
18
0
1
Order By: Relevance
“…For surveys of different measures, see, for example, Isard et al (1960); Bahl, et al (1971); Dixon and Thirwall (1975); Gibbs and Postan (1975); Kruger (2006); Palan (2010). These include the index of regional specialisation (Dixon and Thirlwall, 1975, Krugman;, Shannon's Entropy Index (for example, Aiginger and Davies, 2004;Aiginger and Pfaffermayr, 2004), the Index of Inequality in Production Structure (see Cuadrado--Roura et al, 1999;Haaland et al, 1999;Landesmann, 2000;Percoco et al, 2005), the Theil Index (Brülhart and Traeger, 2005;Ezcurra and Pascual, 2007), and the Hirschman--Herfindahl Index (for example, Sapir, 1996;Davis, 1998;Storper et al, 2002;Aiginger and Pfaffermayr, 2004;Beine and Coulombe, 2007).…”
Section: The Changing Economic Structure Of British Citiesmentioning
confidence: 99%
“…For surveys of different measures, see, for example, Isard et al (1960); Bahl, et al (1971); Dixon and Thirwall (1975); Gibbs and Postan (1975); Kruger (2006); Palan (2010). These include the index of regional specialisation (Dixon and Thirlwall, 1975, Krugman;, Shannon's Entropy Index (for example, Aiginger and Davies, 2004;Aiginger and Pfaffermayr, 2004), the Index of Inequality in Production Structure (see Cuadrado--Roura et al, 1999;Haaland et al, 1999;Landesmann, 2000;Percoco et al, 2005), the Theil Index (Brülhart and Traeger, 2005;Ezcurra and Pascual, 2007), and the Hirschman--Herfindahl Index (for example, Sapir, 1996;Davis, 1998;Storper et al, 2002;Aiginger and Pfaffermayr, 2004;Beine and Coulombe, 2007).…”
Section: The Changing Economic Structure Of British Citiesmentioning
confidence: 99%
“…Various studies have identified an important increase in the level of spatial inequality within the CEE countries during the transition period (Petrakos, 2001;Ezcurra and Pascual, 2007) and the changes seem to have mainly benefited capital cities and major urban agglomerations (Bachtler, Downes and Gorzelak, 1999;Petrakos, 2001). In contrast, most areas specialized in agriculture and 23 manufacturing suffered the negative effects of transition.…”
Section: Modelmentioning
confidence: 99%
“…In literature, the best practices for social inequalities (Benyaklef 1997;Michálek and Podolák 2010) and economic inequalities in regional development (Arndt and Sundrum 1975;Banerjee and Jesenko 2015;Barjak 2001;Buckwalter 1995;Clercq and Naert 1985;Ezcurra and Rodríguez-Pose 2013;Galbraith and Garcilazo 2010;Huang, Kuo and Kao 2003;Pérez-Moreno and Angulo-Guerrero 2016) are scientifically elaborated. Trends in regional polarization and econometric model of regional disparities are successfully described in the article on Baláž (2007), and regional inequalities in the articles (Cardoso 1993;Casellas and Galley 1999;Dunford, Key Laboratory of Regional Sustainable Development Modeling (IGSNRR) and Perrons 2012; Ezcurra and Pascual 2007;Kluvánková-Oravská 2004;Lessmann 2014;Ozornoy 1991;Sawers 2006;Smętkowski 2013;Torrisi et al 2015).…”
Section: Theoretical Background and Contribution Of The Studymentioning
confidence: 99%